Integrated Financial Management Systems on Organizational Performance in Uganda. A Case Study of Kabale Municipal Council. - Tumwebaze, Shaban (Kabale University, 2023)
The purpose of the study was to determine the connection between IFMS and organizational performance in Uganda, specifically as it related to Kabale Municipal Council. The study's three main goals were to: examine the relationship between Kabale Municipal Council's performance and budgeting; examine the relationship between Kabale Municipal Council's performance and commitment controls; and investigate the relationship between Kabale Municipal Council's performance and cash management. The study was carried out after the cross-sectional survey. Data from 152 respondents were collected, and quantitative and qualitative analyses were carried out. Since descriptive analysis requires the presentation of a single variable and its properties, frequency tables were used to represent the data. The bivariate correlations between the predictor components and the dependent variable were examined using a Pearson correlation matrix. A linear regression model was used to fit the data. The regression model's research results show that budgeting (R=0.767), commitment controls (R=0.656), and cash management (R=0.799) all have a favorable effect on Kabale Municipal Council performance. The main conclusion of this study is that budgeting, commitment controls, and financial management have a substantial impact on the organizational performance of Kabale Municipal Council. To evaluate effectiveness at Kabale Municipal Council, the report advises more work on budgeting, commitment controls, and cash management.